How are Critical Thinking Skills and Integration of IPS Problems in Elementary Schools? - Cindy Helda Ferrary; Sekar Purbarini Kawuryan; Herwin (Universitas Pendidikan Ganesha, 2023)
Critical thinking is one of the thinking skills students in 21st-century learning must possess. The reality on the ground shows that the ability to think critically is still relatively low. This study aims to identify social studies learning problems in elementary schools. This research belongs to the pre-experimental research design with a one-shot case study design. The subjects in this study were 5th-grade elementary school students. Data collection in the study was carried out by the test method, with the research instrument being a critical thinking ability test. The data obtained in the study were then analyzed using quantitative descriptive analysis methods. The research analysis results show that the level of student activity, student memory, the application of social studies in everyday life, the ability to identify phenomena, and the complete learning outcomes still need to be improved. Furthermore, students critical thinking skills from basic clarification indicators, assessing basic information support, drawing conclusions, advanced clarification, and applying problem-solving models are also still at a low level, with an average of 44.9%. This preliminary research will be continued into further research to determine the effect of problem-based learning models on students' critical thinking skills.